2012
DOI: 10.1007/s10875-012-9649-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Dose Dexamethasone on Regulating Interleukin-22 Production and Correcting Th1 and Th22 Polarization in Immune Thrombocytopenia

Abstract: These results suggest that HD-DXM may regulate the production of IL-22 in ITP, possibly by correcting Th1 and Th22 polarization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…For example, the chemokine CX3CL1/fractalkine known for its ability to promote the survival of CD16 ϩ monocytes 37 was elevated, albeit not statistically significant, in blood and bone marrow of ITP patients. 38 The expansion of CD16 ϩ monocytes (our study) and/or their potential heightened activation state 34 in ITP may be responsible for the previously described skewed Th1 responses, [12][13][14]26 which was also confirmed in this study. We did not analyze platelet antigen-specific Th1 responses, but our working hypothesis is that the increase in Th1 responses will ultimately augment antigenspecific Th1 responses through positive feedback mechanisms.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…For example, the chemokine CX3CL1/fractalkine known for its ability to promote the survival of CD16 ϩ monocytes 37 was elevated, albeit not statistically significant, in blood and bone marrow of ITP patients. 38 The expansion of CD16 ϩ monocytes (our study) and/or their potential heightened activation state 34 in ITP may be responsible for the previously described skewed Th1 responses, [12][13][14]26 which was also confirmed in this study. We did not analyze platelet antigen-specific Th1 responses, but our working hypothesis is that the increase in Th1 responses will ultimately augment antigenspecific Th1 responses through positive feedback mechanisms.…”
Section: Discussionsupporting
confidence: 83%
“…21 More recently, studies reported increased Th17 cells or IL-17 cytokine in ITP patients, [22][23][24] implicating a possible role for Th17 cells in ITP immunopathology, although 2 reports did not detect any difference. 25,26 Among the treatment options available to ITP patients, the recently licensed thrombopoietic agents, by increasing platelet production, have yielded overall durable responses in patients with persistent, chronic, and/or refractory ITP while on treatment. 27 Interestingly, improved Treg function in ITP patients was associated with increased platelet counts after the use of these agents, 28 despite apparent lack of immunomodulatory activity associated with such agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Th1 cells from patients with immune thrombocytopenia are sensitive to glucocorticoid inhibition [69]. Similarly, glucocorticoids decrease Th2 cytokines IL-4, IL-5, and IL-13 in vitro [70, 71] as well as Th2 cytokines in T cells from asthma patients [72].…”
Section: Distinct Sensitivity Of Th Cytokines To Glucocorticoid Sumentioning
confidence: 99%
“…Treatment with GCs reduces the frequency of peripheral blood IL-22 T cells and the levels of plasma IL-22 in patients with acute bacterial infection [21]. High-dose dexamethasone reduced IL-22 production in immune thrombocytopenia [22]. CYC is a well-established immunodepressant known to influence cell cycle and DNA synthesis.…”
Section: Discussionmentioning
confidence: 99%